ANALISIS SPASIAL SEBARAN PENYAKIT MENULAR KOTA MAKASSAR TAHUN 2018 - Sukarna, Sukarna; Awi, Awi; Sutamrin, Sutamrin (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
Population density correlates spatially with various aspects of community life, such as the number of people with infectious and non-infectious diseases, seasonal (endemic) or non-seasonal (epidemic), mild or severe, and regular or rare. This research focuses on 8 infectious diseases, namely measles, diphtheria, diarrhea, typhoid, malaria, helminthiasis, TB, and DHF. Data on infectious diseases in 2018 were obtained from the Makassar City Health Service Office, which was sourced from 46 puskesmas throughout Makassar City. The results of this study are (1) The limited data, thus, this study focuses on only 8 diseases; (2) Based on the results of the analysis of univariate cluster Moran index, there are (a) the two highest warnings of disease distribution attributed to the districts, namely diarrhea (in Sangkarrang, Ujungtanah, and Mariso) and helminthiasis (in Singkarang); (b) patterns of spread of infectious diseases (this article shows only one thematic map of disease) and spread from nothing significant to very significant; (c) the spread of infectious diseases appears uneven in each district and tends to occur in certain districts, such as (i) Measles have 3 districts (Biringkanaya, Tamalanrea, and Bontoala), (ii) Diphtheria there are 2 districts (Tamalanrea and Biringkanaya), ( iii) Diarrhea only in Panakkukang District, (iv) Malaria only in Ujungtanah, (v) Worms in 4 districts (Manggala, Rappocini, Makassar, and Ujungpandang), (vi) DHF only in Panakkukang District, (vii) Typhoid and TB are not significant.